STATE-OF-THE-ART 3D ACQUISITION AND IMAGING IN ULTRA-SHALLOW WATER IN THE NORTHWESTERN PART OF THE BLACK SEA - TYSHCHENKO, Andrii; VYZHVA, Andrii; MELNYK, Leonid; TEGNANDER, Jonas Fagerli; KITTELL, Lars-Erik; HELGEBOSTAD, Kristian Svarva (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. The paper discusses the acquisition and imaging (PSDM+FWI) of 3D seismic data in the ultra-shallow waters of the Black Sea's northwestern shelf, focusing on the Dolfin Inner shelf license areas. Despite depths ranging from 14m to 40m, an efficient acquisition setup has been chosen to navigate seafloor obstacles.Methods. GeoStreamer data has allowed more advanced imaging options. Access to separated wavefield components has permitted us to include advanced processing technologies. The data underwent advanced processing, including 3D wavefield separation, deghosting, demultiple, and machine learning-guided denoising.Results. Results demonstrate the final migration velocity model's (with FWI) ability to capture high and low velocity contrasts critical for depth imaging. Separated wavefield imaging (SWIM) enhances imaging of the seafloor providing a very good match with bathymetry data. SWIM also allows acquiring high-resolution images of the shallow water area, which opens up the possibility of using this data for wind farm siting and hydrogen exploration.Сonclusions. Comparing 2D and 3D seismic data emphasizes the latter's superior quality, crucial for evaluating the Dolfin Inner shelf area's hydrocarbon potential. Next study will focus on the exploration in the Outer Shelf and adjacent deepwater domains, highlighting the Black Sea's Ukrainian waters as a promising frontier for oil and gas exploration. The acquired 3D seismic data plays a pivotal role in advancing this exploration, contributing valuable insights in a cost-effective manner.
Keywords: acquisition; depth imaging; ultra-shallow water; FWI; SWIM; PSDM; Black Sea; Machine learning